2020
DOI: 10.3390/s20185181
|View full text |Cite
|
Sign up to set email alerts
|

What Features and Functions Are Desired in Telemedical Services Targeted at Polish Older Adults Delivered by Wearable Medical Devices?—Pre-COVID-19 Flashback

Abstract: The emerging wearable medical devices open up new opportunities for the provision of health services and promise to accelerate the development of novel telemedical services. The main objective of this study was to investigate the desirable features and applications of telemedical services for the Polish older adults delivered by wearable medical devices. The questionnaire study was conducted among 146 adult volunteers in two cohorts (C.1: <65 years vs. C.2: ≥65 years). The analysis was based on qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
10
0
3
Order By: Relevance
“…In Poland, older adults, including people with dementia, are often alienated from technological progress [ 75 ], which causes difficulties in benefitting from remote support provision [ 6 , 76 ], including social and medical care. To date, knowledge about and usage of telemedicine in Poland have been limited [ 77 ]. Testing this solution suddenly and widely during the lockdown has highlighted barriers to its successful implementation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Poland, older adults, including people with dementia, are often alienated from technological progress [ 75 ], which causes difficulties in benefitting from remote support provision [ 6 , 76 ], including social and medical care. To date, knowledge about and usage of telemedicine in Poland have been limited [ 77 ]. Testing this solution suddenly and widely during the lockdown has highlighted barriers to its successful implementation [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further qualitative research can, for example, involve focus group discussion on the issues identified but insufficiently elaborated in the analyzed interviews. Such an example could be remote communication in dementia care—a topic which, although present in earlier research [ 77 , 83 ], takes on a new meaning in the face of the COVID-19 pandemic [ 76 , 78 , 79 , 80 ]. Another issue worth exploring further in a quantitative design is coping strategies classified as a sub-theme of psychological response.…”
Section: Discussionmentioning
confidence: 99%
“…The "right function(s)" is largely dependent on the end-users and beneficiaries of the WSDs (i.e., field workers and management staff). The need for personalized wearable monitoring has recently come to the forefront in construction and adjacent industries, which share some similarities [17,33,34], necessitating the need to explore the types of WSD function that workers are open to having and the minimum number and type of functions needed for the management to make informed decisions (and functions that justify investing in WSDs) before implementation [35]. It is, therefore, important to assess if the design of WSDs should incorporate functions that provide personal feedback of sensitive (or private) information, predominantly physiological metrics, to the primary users (i.e., workers) and non-sensitive information (such as environmental metrics) to secondary users (e.g., safety manager) so that appropriate actions and interventions can be taken by concerned parties to prevent potential injuries or accidents.…”
Section: Wsd Functions and Applications In Constructionmentioning
confidence: 99%
“…We believe that data from wearable devices (such as smartwatches or fitness trackers) can be an auxiliary tool to assist teleconsultation with primary care physicians, especially in emergencies or health crises, because they may collect health data in the home setting, which can play an essential role in patient diagnosis or screening. Our previous work focused on investigating the desirable features and applications of telemedical services for the older adults delivered by wearable medical devices [ 3 ]. At present, smartwatches and fitness trackers are used to quantify physical activity and sleep quality with the primary goal of improving overall health.…”
Section: Introductionmentioning
confidence: 99%